Isoproterenol-Induced Cardiac Diastolic Dysfunction in Mice: A Systems Genetics Analysis - Wang, Jessica; Huertas-Vazquez, Adriana; Wang, Yibin; Lusis, Aldons J. (Frontiers in Cardiovascular Medicine, 2019)
We examined an isoproterenol heart failure model across a panel of diverse inbred strains of mice, the Hybrid Mouse Diversity Panel (HMDP), using left atrial (LA) and lung weights as well as echocardiogram parameters as surrogates for cardiac diastolic function. We identified gene transcripts that significantly correlated with diastolic function. In addition, we mapped echocardiographic parameters associated with diastolic function. We identified a locus near Tns3-Hus1 to be associated with baseline E/A ratio in mice (p-value = 1.65E-06), the syntenic region of which was recently associated with E/A ratio in a genome-wide association study (GWAS) meta-analysis of the EchoGen consortium in humans. We also identified a locus near Cdkn2a-Cdkn2b, which is a region syntenic to the human 9p21 locus, to be associated with week 3 A/E ratio (p-value = 2.15E-06). Our study is the first study to map diastolic dysfunction in mice, in which a locus was found to be shared with a recent human GWAS on diastolic function. Moreover, our cardiac transcriptome correlation and eQTL analysis generated hypotheses for future basic investigations. These results showed that, although technical and physiological challenges limit diastolic function assessment in mice and humans, future investigations examining the genetic architecture of diastolic function among a diverse mouse population, such as the HMDP, in controlled experimental settings, offer distinct advantages in understanding the genetic determinants of diastolic function.